AN ANALYSIS OF SYNTACTICAL ERRORS IN WRITING MADE BY THE STUDENTS OF ENGLISH EDUCATIONAL DEPARTMENT AT PGRI UNIVERSITY OF BANYUWANGI - Inayah, Arin; Karina Alfi Nuril Layli; Wiwin Indiarti (LUNAR, 2024)
This research described about an analysis of Syntactical Errors in writing cause and effect paragraphs made by the 2nd semester students of English Educational Department at PGRI University of Banyuwangi. The purpose of this research was to analyze the types and the dominant forms of Syntactical Errors in students’ cause and effect paragraphs. The researcher used a descriptive qualitative method in analyzing the data. The sources of data in this research were cause and effect paragraphs made by 2nd semester students of English Educational Department at PGRI University of Banyuwangi. The researcher used Politzer and Romirez’s theory as a base for analyze the Syntactical Errors of the data. From the analysis, the researcher discovered that there were 45 different types of Syntactical Errors based on the data analysis and discussion. Students made errors in 33 types of noun phrases and 12 types of verb phrases. The errors can be percentage to 73% of noun phrases and 27% of verb phrases. From the percentages, the errors are dominated by noun phrases by 73% of the total Syntactical Errors found in writing cause and effect paragraphs made by the 2nd Semester Students of English Educational Department at PGRI University of Banyuwangi.